2006
DOI: 10.4489/myco.2006.34.3.138
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Cyanobacteria (Blue-Green algae) from Rice Paddy Soil for Antifungal Activity against Plant Pathogenic Fungi

Abstract: Soil cyanobacteria isolated from the rice paddy fields of 10 different locations across Korea were evaluated by agar plate diffusion test for antifungal activity. Aqueous, petroleum ether, and methanol extracts from one hundred and forty two cyanobacterial strains belonging to the 14 genera were examined for antifungal properties against seven phytopathogenic fungi causing diseases in hot pepper (Capsicum annuum L). Of total cyanobacteria, nine cyanobacteria (6.34%) exhibited antifungal effects. The nine cyano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 22 publications
2
36
0
1
Order By: Relevance
“…There are reports on antimicrobial effects from microalgal aqueous and organic solvent extractand have been visualized in bioassays using selected microorganisms. In the investigations, microalgae have demonstrated the antimicrobial effects of many strains likeNostoc, Anabaena, Synechococcus, Oscillatoriaagainst a variety of microbes.Kim 10 showed that 50% of the microalgae genera existed in heterocytous filament form. A total of 100 such samples were taken against 10 different strains of fungi and proved to have fungicidal activity.…”
Section: Resultsmentioning
confidence: 99%
“…There are reports on antimicrobial effects from microalgal aqueous and organic solvent extractand have been visualized in bioassays using selected microorganisms. In the investigations, microalgae have demonstrated the antimicrobial effects of many strains likeNostoc, Anabaena, Synechococcus, Oscillatoriaagainst a variety of microbes.Kim 10 showed that 50% of the microalgae genera existed in heterocytous filament form. A total of 100 such samples were taken against 10 different strains of fungi and proved to have fungicidal activity.…”
Section: Resultsmentioning
confidence: 99%
“…and Rhizoctonia solani (Kulik, 1995). In a previous study (Kim, 2006), antifungal activities were found in 29 strains of the 298 microalgal strains tested. Nostoc communm FA-103 was selected as the subject of this study because of its broad spectrum of antifungal activity on plant pathogenic fungi, especially F. oxysporum f. sp.…”
mentioning
confidence: 84%
“…Bacteria have been reported to associate with a variety of fungi including mushrooms. Antifungal agents produced by some bacteria have shown to be beneficial to control pathogenic fungi (Kim, 2006; Chang and Kim, 2007). However, they are harmful for the mushroom industry in general.…”
mentioning
confidence: 99%